Penanaman Nilai-Nilai Pendidikan Akhlak Di SMP Negeri 9 Surakarta - Hidayatul Layl Umi Syukron; Safana Fauziyah; Intan Nur Amalia; Faritsa Azzahra (LPPM Politeknik Pratama, 2024)
Cultivation is the process of instilling beliefs, attitudes and values in a person so that these values influence his behavior (moral behavior). Values are general principles that help people in society judge and choose certain actions and principles. Moral education is an effort to improve various human potentials, including physical, mental, attitude and conscience through teaching, guidance and training in accordance with Islamic values to prevent bad behavior. The aim of this research is to find out how the counseling guidance program instills moral education values in students at SMP N 9 Surakarta. The method used in this research uses qualitative methods. The research subject was a guidance and counseling teacher. Observation and documentation are data collection methods. The results of the research that has been conducted show that guidance and counseling teachers use classical service programs and habituation as an effort to instill educational values that are in accordance with the students' religion.